Effects of Interferon-Alpha Treatment on the Incidence of Hyperglycemia in Chronic Hepatitis C Patients: A Systematic Review and Meta-Analysis - Zhang, Wei; Rao, Hui-Ying; Feng, Bo; Liu, Feng; Wei, Lai (PLOS ONE, 2012)
Background There is a significant association between effects of interferon-alpha treatment and the risk of developing hyperglycemia in patients with chronic hepatitis C virus (HCV) infection. The objective of this systematic review and meta-analysis on the basis of published observational studies was to estimate risk of hyperglycemia in chronic HCV patients who had acquired sustained virological responses (SVR) compared to those without SVR. Methodology We identified eligible studies by searching the relevant databases, including PubMed, Embase, and Google, for papers published between January 1990 and April 2011. The selection of eligible papers was carried out using a scoring system based on guidelines and inclusion criteria that were established before the articles were identified. Heterogeneity across studies was determined and the meta-analysis was performed following standard guidelines. Conclusions Eleven eligible studies provided data of the incidence of hyperglycemia in chronic hepatitis C patients with SVR in comparison with patients without these conditions. The results demonstrated that SVR was associated with a lower risk of hyperglycemia (odds ratio = 0.497, 95% confidence interval 0.421–0.587, p<0.001), and there was no evidence of any substantial between-study heterogeneity (I2 = 24.4%, p>0.1). Results of meta-regression showed patients with different baseline glucose (normal vs. abnormal) and patients with co-infected HIV (presence vs. absence) as the sources of low heterogeneity (p<0.15).The lowest risk of hyperglycemia was described in patients with normal glucose baseline (OR = 0.402, 95%CI 0.297–0.543, p<0.001). This is the first systematic review and meta-analysis performed to examine the association between SVR and risk of hyperglycemia in patients with HCV infection. Our meta-analysis suggests that SVR reduce the risk of developing glucose abnormalities, especially in patients with normal glucose baseline.